2004
DOI: 10.1002/hup.589
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary caffeine on mood when rested and sleep restricted

Abstract: Prolonged use of caffeine can lead to physical dependence evidenced by characteristic withdrawal symptoms during abstinence. Debate exists as to whether mood enhancement by caffeine represents a net effect or merely the restoration of abstinence-induced mood decrements. One aim of this study was to determine the net effects on mood of dietary caffeine compared with prolonged abstinence. In addition, the study aimed to determine whether caffeine restores mood degraded by a non-caffeine source, namely, sleep res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 39 publications
5
34
0
2
Order By: Relevance
“…The overall results are consistent in all important respects with the withdrawal reversal hypothesis, and are supported by other recent studies showing enhancing effects only in persons who are caffeine deprived [e.g. 7,11,[18][19][20][21][22] . That is, a substantial body of evidence now exists indicating that improvements in human performance and mood, long held to be primary effects of dietary caffeine, are more readily attributable to reversal of the withdrawal effects that accompany brief abstinence.…”
Section: Discussionsupporting
confidence: 79%
“…The overall results are consistent in all important respects with the withdrawal reversal hypothesis, and are supported by other recent studies showing enhancing effects only in persons who are caffeine deprived [e.g. 7,11,[18][19][20][21][22] . That is, a substantial body of evidence now exists indicating that improvements in human performance and mood, long held to be primary effects of dietary caffeine, are more readily attributable to reversal of the withdrawal effects that accompany brief abstinence.…”
Section: Discussionsupporting
confidence: 79%
“…15 Caffeine has been associated with increases in several cardiovascular disease risk factors, 16,17 such as higher blood pressure (BP), an acute effect of coffee. 18 In contrast, recent studies have reported health benefits associated with coffee consumption. 19,20 At low doses, caffeine improves hedonic tone and reduces anxiety, while it produces an increase in tense arousal, including anxiety, nervousness, and jitteriness, at high doses.…”
Section: Introductionmentioning
confidence: 72%
“…Caffeine enhances physiological arousal, by activating both the sympathetic nervous system by increasing heart rate and blood pressure (Davidson and Smith 1991;Green and Suls 1996;James and Gregg 2004) and the hypothalamic pituitary adrenal axis by increasing cortisol (Lovallo et al 1996(Lovallo et al , 2005. Caffeine exerts physiological effects similar to those of acute stress (Gerra et al 2001;Kudielka et al 2004) and may augment the physiological stress response (Lovallo et al 2006).…”
Section: Introductionmentioning
confidence: 99%